Health systems strengthening through policy-level integration of community health worker programs into national health systems for improved health outcomes - scorecard metrics validation: A bifactor structural equation model approach - Mupara, Lucia Mungapeyi; Mogaka, John Jules O.; Brieger, William R.; Tsoka-Gwegweni, Joyce M. (Frontiers in Public Health, 2022)
Background: Subsequent to the demonstrated potential of Community Health Workers (CHWs) in strengthening health systems to improve health outcomes, recent literature has defined context and guidelines for integrating CHWs programs into mainstream health systems. However, quantitative measures for assessing the extent of CHW programs integration into national health systems need to be developed. The purpose of this study was to validate a newly developed scale - Community Health Workers Program Integration Scorecard Metrics (CHWP-ISM) - for assessing the degree of integration of CHWs programs into national health systems in Sub-Saharan Africa (SSA). Methods: Data obtained through a pilot study involving a purposively selected sample of forty-one participants selected from populations involved in CHW programs work in selected countries of SSA formed the basis of a 31-item bifactor model. Data was collected between June and December 2019. Applying a latent variable approach implemented with structural equation modelling, data analysis was mainly done in R statistical environment, applying factor analysis procedures. Results: Dimensionality, construct validity and the CHWP-ISM scale’s internal consistency were assessed. Confirmatory factor analysis of the CHW-ISM bifactor model supported a co-occurring CHW integration general factor and six unique domain-specific factors. Both comparative fit index (CFI) and Tucker–Lewis Index (TLI) fit indices were above 0.9, while root mean square of the residuals (RMSR) was 0.02. Cronbach’s alpha (α), Guttman 6 (Lambda 6) and Omega total (ωt) were above 0.8, indicating good scale reliability. Conclusion: Statistical significance of the bifactor model suggests CHW integration has to be examined using factors that reflect a single common underlying integration construct, as well as factors that reflect unique variances for the identified six subject-specific domains. The validated CHWP-ISM could be useful to inform policy advisers, health systems, donors, non-governmental organizations, and other CHW programs stakeholders with guidance on how to quantitatively assess the integration status of different components of CHW programs into respective critical functions of the health system. Improved integration could increase CHW programs functionality that could in turn strengthen the health care systems to improve health outcomes in the region.